Using SQ3R Method to Improve Reading Comprehension of the Students XI Class of SMA ITMA Jombang - Akhmad Kanzul Fikri (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2015)
This study is classified as a classroom action research (CAR). This study proposed in term of survey, question, read, recite and review (SQ3R) in the English reading comprehension of the students XI class of SMA ITMA Jombang to solve the students’ incompetency on reading skill. As the result of the preliminary study, the researcher found the following information: a) The teacher still used teacher-oriented method, b) Students have low understanding in reading English text; c) Students could not comprehend the difficult text, d) Students were inactive and lack of motivation to read an English text. Therefore, the criteria of success were arranged to those problems. The result in this research showed that by implementing SQ3R as the reading method in two cycles, the students’ reading skill was improved and then their participation in the classroom were highly developed. KEYWORDS: Cooperative Learning, SQ3R (Survey, question, read, review and recite), Reading Skill